2018
DOI: 10.30634/2414-2077.2015.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Olive Oil Mill Wastewater by UV-Light and UV/H2O2 System

Abstract: Olive oil mills generates large volumes of wastewaters (OMW). The absence of legislation, which manages and obligates the treatment of OMW has led to the creation of large build-evaporation ponds as a solution for this environmental problem. The function of these ponds is the evaporation of wastewater during summer months. However, evaporation isn't enough to eliminate all wastewater in the rafts and this fact allows the generation of a great volume of concentrate wastewater with high organic load (COD = 0.5-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this sense, and in order to define the effect of the combination or not among UV light, oxidant and catalyst in the same system, it could be indicated that the removal percentages were increased according to the following sequence UV < UV/H 2 O 2 < UV/FeCl 3 /H 2 O 2 . The final percentages reached for the parameters TC, TOC and TN have been for only UV-light 43.3%, 34.3% and 40.0%, for UV/H 2 O 2 system 42.9%, 38.4% and 45.3% [5] and for the system UV/FeCl 3 /H 2 O 2 , 71.8%, 57.9% and 67.9%, respectively. These resulted were obtained using OMW with similar initial TOC value = 3929 mg/L.…”
Section: Selection Of Catalystmentioning
confidence: 94%
See 3 more Smart Citations
“…In this sense, and in order to define the effect of the combination or not among UV light, oxidant and catalyst in the same system, it could be indicated that the removal percentages were increased according to the following sequence UV < UV/H 2 O 2 < UV/FeCl 3 /H 2 O 2 . The final percentages reached for the parameters TC, TOC and TN have been for only UV-light 43.3%, 34.3% and 40.0%, for UV/H 2 O 2 system 42.9%, 38.4% and 45.3% [5] and for the system UV/FeCl 3 /H 2 O 2 , 71.8%, 57.9% and 67.9%, respectively. These resulted were obtained using OMW with similar initial TOC value = 3929 mg/L.…”
Section: Selection Of Catalystmentioning
confidence: 94%
“…In this sense, when only photolysis (UV-light) was applied ( Figure 1B), the initial organic load is independent of the final removal percentages registered. In addition, Hodaifa et al [5] developed photo-oxidation of OMW using UV/H 2 O 2 system at similar conditions to that used in this work but without a catalyst (initial COD = 1944.2 mg O 2 /L, initial H 2 O 2 concentration = 10% (w/v), stirring speed = 150 rpm, T = 20 • C and pH = 3). In this sense, and in order to define the effect of the combination or not among UV light, oxidant and catalyst in the same system, it could be indicated that the removal percentages were increased according to the following sequence UV < UV/H 2 O 2 < UV/FeCl 3 /H 2 O 2 .…”
Section: Selection Of Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…(14) studied the use of UV, H2O2 /UV and ozone in treatment of pharmaceuticals wastewater and they found that ozonation was the most effective process among the three tested processes. (15) (16). Their results showed that COD and TOC removal using UV were 22 and 34% respectively, while they were 48% for both COD and TOC when using UV / H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%